2020
DOI: 10.21037/gs.2020.01.20
|View full text |Cite
|
Sign up to set email alerts
|

Implant-based immediate breast reconstruction: failure rate when radiating the tissue expander or the permanent implant—a meta-analysis

Abstract: Background: Implant-based immediate approach remains to be a first line option for reconstruction of mastectomy defects. When combined with post-mastectomy radiation therapy (PMRT) two different schemas are possible: radiating the temporary tissue expander (TTE) or the permanent implant (PI). The present article intends to be the biggest cohort meta-analysis to the date comparing reconstructive failure (RF) rate in these two scenarios: PMRT to TE compared with PMRT to PI.Methods: A systematic search of the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
(62 reference statements)
1
2
0
Order By: Relevance
“…Body mass index and size of tissue expanders increased the odds of 2-year complications. These findings were partially in line with the results of a recent meta-analysis, 31 which revealed that early exchange less than 3 months, 32 size of permanent implant, 3 advanced stage requiring chemotherapy, 32 and use of chest wall radiotherapy boosts were significant variables predicting reconstructive failure after postmastectomy radiation therapy. 33 The review revealed other potential risk factors, such as smoking status, 10 age older than 55 years, 34,35 low or high body mass index, 1,32 body weight, diabetes, nipple-sparing mastectomies, inframammary fold approach, and partial coverage of expanders or permanent implants.…”
Section: Discussionsupporting
confidence: 87%
“…Body mass index and size of tissue expanders increased the odds of 2-year complications. These findings were partially in line with the results of a recent meta-analysis, 31 which revealed that early exchange less than 3 months, 32 size of permanent implant, 3 advanced stage requiring chemotherapy, 32 and use of chest wall radiotherapy boosts were significant variables predicting reconstructive failure after postmastectomy radiation therapy. 33 The review revealed other potential risk factors, such as smoking status, 10 age older than 55 years, 34,35 low or high body mass index, 1,32 body weight, diabetes, nipple-sparing mastectomies, inframammary fold approach, and partial coverage of expanders or permanent implants.…”
Section: Discussionsupporting
confidence: 87%
“…Immediate breast reconstruction has shown satisfactory aesthetic results and overall psychological well-being compared with delayed breast reconstruction. [ 4 ] Moreover, previous studies support the oncological safety of immediate breast reconstruction following total mastectomy. [ 5 , 6 ] Similar to the United States, implant-based breast reconstruction (IBR) is the most prevalent form of breast reconstruction in China, partly because of minimal donor site sacrifice and thus faster postoperative recovery, as well as a shorter learning curve, which is favored by more doctors and patients.…”
Section: Introductionmentioning
confidence: 84%
“…Several published evidences had revealed contradictory findings regarding the cosmetic outcomes and complication rates with different types of IBBR surgery after PMRT. [14][15][16] Currently, with the increased delivery of PMRT along with an increased demand of IBBR in patients with stages II-III disease, oncologic and plastic surgeons need to recognize the distinct IBBR surgical methods in selected patients with PMRT. However, studies remain limited for identification of appropriate IBBR modality for patients administering PMRT, especially in China.…”
Section: Introductionmentioning
confidence: 99%
“…When PMRT is required, the ideal types of reconstructive surgery remain unclear. Several published evidences had revealed contradictory findings regarding the cosmetic outcomes and complication rates with different types of IBBR surgery after PMRT 14–16 …”
Section: Introductionmentioning
confidence: 99%